The Urgency of Law Enforcement Regarding The Existence of Subsidiaries as a Form of Avoidance of Laws Prohibiting Monopoly Practices and Unfair Business Competition - Dwi Natalia Martama Hutabarat; Martono Anggusti; Jinner Sidauruk (Dinasti Research, 2025)
This research analyzes the legal position of subsidiaries in the context of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The main focus of the research is to identify legal loopholes in subsidiary regulations that can be exploited for monopolistic practices and unfair business competition, as well as formulating legal remedies to address them. The research uses a normative juridical method with a case study approach to Lion Group Airlines. The results show that the regulation of group companies, which is still based on the 2007 Company Law with a single company approach, has created legal loopholes that allow monopolistic practices through subsidiaries. This is evident in the Lion Group Airlines case, where discriminatory practices occurred through exclusive agreements between the parent company and its subsidiaries, which harmed other business actors. To address these issues, several legal measures are needed, including: (1) prohibiting manipulation of company organs through corporate actions, (2) establishing a special supervisory body, (3) prohibiting market manipulation through subsidiaries, (4) implementing reversed burden of proof for negative market impacts, and (5) nullifying agreements that result in unfair competition. This research recommends the need for revision of Law No. 5 of 1999 to regulate more comprehensively about monopolistic practices through subsidiaries and strengthen supervision of corporate actions.